TLR4, NOD1 and NOD2 mediate immune recognition of putative newly identified periodontal pathogens. (10th September 2015) - Marchesan, J.; Jiao, Y.Z.; Schaff, R.A.; Hao, J.; Morelli, T.; Kinney, J.S.; Gerow, E.; Sheridan, R.; Rodrigues, V.; Paster, B.J.; Inohara, N.; Giannobile, W.V.
Summary: Periodontitis is a polymicrobial inflammatory disease that results from the interaction between the oral microbiota and the host immunity. Although the innate immune response is important for disease initiation and progression, the innate immune receptors that recognize both classical and putative periodontal pathogens that elicit an immune response have not been elucidated. By using the Human Oral Microbe Identification Microarray (HOMIM), we identified multiple predominant oral bacterial species in human plaque biofilm that strongly associate with severe periodontitis. Ten of the identified species were evaluated in greater depth, six being classical pathogens and four putative novel pathogens. Using human peripheral blood monocytes (HPBM) and murine bone‐marrow‐derived macrophages (BMDM) from wild‐type (WT) and Toll‐like receptor (TLR)‐specific and MyD88 knockouts (KOs), we demonstrated that heat‐killed Campylobacter concisus, Campylobacter rectus, Selenomonas infelix, Porphyromonas endodontalis, Porphyromonas gingivalis, and Tannerella forsythia mediate high immunostimulatory activity. Campylobacter concisus, C. rectus, and S. infelix exhibited robust TLR4 stimulatory activity. Studies using mesothelial cells from WT and NOD1‐specific KOs and NOD2‐expressing human embryonic kidney cells demonstrated that Eubacterium saphenum, Eubacterium nodatum and Filifactor alocis exhibit robust NOD1 stimulatory activity, and that Porphyromonas endodontalis and Parvimonas micra have the highest NOD2 stimulatory activity. These studies allowed us to provide important evidence on newly identified putative pathogens in periodontal disease pathogenesis showing that these bacteria exhibit different immunostimulatory activity via TLR4, NOD1, and NOD2 (Clinicaltrials.gov NCT01154855).